Pesantren-Based Principal Leadership Symbolic Interactionism Perspective in Schools - Wardi, Moh; Rusli, Rusli; Mundiri, Akmal; Batul, Zahroil (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2023)
This study aims to discover the symbolic interactionism perspective of teachers or subordinates towards the principal at SMA Nurul Jadid. To achieve the objectives of this study, researchers used a qualitative approach, with a type of phenomenological research. The subjects in this study were teachers and subordinates at Nurul Jadid High School. At the same time, data collection is done through interviews and observation. The study results show that the leadership behaviour of the principal at SMA Nurul Jadid leads to transformational leadership based on intelligent and breakthrough social communication. The process of symbolic interaction between the teacher or subordinates and the principal of a pesantren-based school is mediated by the values used to represent an object. The values that are built include; the value of integrity, the value of simplicity, and the value of dedication. These values occur based on the subordinate's meaning of the principal's behaviour, which creates a symbolic world at Nurul Jadid Paiton Probolinggo High School.